Acute triangle A B C has its vertices labeled in a clockwise manner. It is rotated 9 0 ∘ counter-clockwise about C to get A ’ B ’ C . Let D be the midpoint of A B ’ . If ∣ B A ’ ∣ = 1 2 0 2 , what is ∣ C D ∣ ?
Details and assumptions
∣
X
Y
∣
denotes the straight line distance from
X
to
Y
.
Due to the rotation in the question, I am explicitly denoting that we are measuring the straight line distances, as opposed to the arc length of the sector.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let C be the origin and A and B are on the 2nd quadrant.
A = z 1 and B = z 2 and C = 0
Rotating counter-clockwise by C is equivalent of multiplying A and B by i = e i π / 2
So, A ′ = i ∗ z 1 B ′ = i ∗ z 2
D = ( z 1 + i ∗ z 2 ) / 2
⇒ ∣ C D ∣ = ∣ ( z 1 + i ∗ z 2 ) / 2 ∣
= ∣ i ∣ ∗ ∣ ( z 1 + i ∗ z 2 ) / 2 ∣
= ∣ ( i ∗ z 1 − z 2 ) / 2 ∣
= ∣ A ′ B / 2 ∣
= 1 2 0 2 / 2
= 6 0 1
Solution: ∣ C D ∣ = 6 0 1
Nice one Dude!!!!!!
Let the point C be at origin ( 0 , 0 ) , the other points be at A ( x , y ) and B ( z , 0 ) . Rotating 90 degree counter-clockwise about C, we get A'B'C. The coordinate of A' will be ( y , − x ) , as CA' is perpendicular to CA. Similarly the coordinate of B' will be ( 0 , − z ) . The coordinate of D is 2 x , 2 y − z . We are given, ( y − z ) 2 + x 2 = 1 2 0 2 Hence, C D = ( y − z ) 2 + x 2 / 2 = 6 0 1
First, rotate triangle A B ′ C 9 0 ∘ counter-clockwise about C to form A ′ ′ B ′ ′ C . D is then mapped to D ′ . Note that A ′ ′ = A (obvious), and that B C B ′ ′ is collinear (since ∠ B C B ′ = ∠ B ′ C B ′ ′ = 9 0 ∘ ). Now we compare triangles B ′ ′ C D ′ and B ′ ′ B A ′ . Since ∣ B ′ ′ C ∣ = ∣ C B ∣ and ∣ B ′ ′ D ′ ∣ = ∣ D ′ A ′ ∣ , we know that ∣ B ′ ′ B ∣ ∣ B ′ ′ C ∣ = ∣ B ′ ′ A ′ ∣ ∣ B ′ ′ D ∣ = 2 1 . Also both triangles share a common angle B B ′ ′ A , so they're similar. Therefore, ∣ B A ′ ∣ ∣ C D ′ ∣ = 2 1 . Hence ∣ C D ∣ = ∣ C D ′ ∣ = 2 1 × 1 2 0 2 = 6 0 1 .
let B(a,o) >let A(x,y) then B'(0,a) >then A'(-y,x) from distance formula:- (x x +(a+y) (a+y))=(1202) (1202) -------------(1) (OC) (OC)=((x/2) (x/2)+(a/2+y/2) (a/2+y/2)) FROM ----(1) OC =1202/2=601//
Extend C D to a point E such that C D = D E . Also, it is given that A D = D B and by opposite angles, ∠ A D C = ∠ E D B ′ . Thus, triangles E D B ′ and C D A are congruent. Also, ∠ D E B ′ = ∠ D C A , which implies that E B ′ ∥ A C . By a similar argument, triangles C D B ′ and E D A are congruent, which shows E A ∥ B ′ C . Therefore, A E B ’ C is a parallelogram. Since A E = C B ’ = C B , A C = C A ’ , ∠ C A E = 1 8 0 ∘ − ∠ A C B ’ = 9 0 ∘ + ( 9 0 − ∠ A C B ′ ) = 9 0 ∘ + ∠ A C B = ∠ B C A ’ , hence triangles A C E and C A ’ B are congruent. Thus, C D = 2 1 C E = 2 1 A ’ B = 6 0 1 .
Note: It doesn't matter if A B C is labeled clockwise or anti-clockwise. Similarily, it doesn't matter if the rotation is clockwise or anti-clockwise. A direction is specified to avoid ambiguity in the above solution.
Problem Loading...
Note Loading...
Set Loading...
Since the triangle A ′ B ′ C is formed by rotating A B C 90 degree counter-clockwise acbout C , so the two triangles A ′ B ′ C and A B C are equal. Thus B ′ C = B C and A ′ C = A C .
Let E be the point on C D extended such that E D = C D . We have C E and B ′ A bisect each other at D , so A C B ′ E is a parallelogram. This implies A E = B ′ C = B C ; and ∠ E A C + ∠ B ′ C A = 1 8 0 ∘ . On the other hand, 1 8 0 ∘ = 9 0 ∘ + 9 0 ∘ = ∠ B ′ C B + ∠ A ′ C A = ∠ B ′ C A + ∠ B C A ′ . Hence, ∠ E A C = ∠ B C A ′ . Together with the conclusions above that A C = A ′ C and A E = B C , so the two triangles A ′ C B and C A E are equal by S.A.S. Thus, A ′ B = C E = 2 C D , which gives the answer ∣ C D ∣ = 6 0 1 .